VD_FINDINFO ML / 2019 / 119 vom 27. Juni 2019 - VD Tribunal cantonal (2019)
MAINLEVÉE PROVISOIRE, TITRE DE MAINLEVÉE, BAIL À LOYER, DÉFAUT DE LA CHOSE | 258 al. 2 CO, 258 CO, 259a CO, 82 al. 1 LP, 82 al. 2 LP, 82 LP